2015
DOI: 10.1177/1932296814566232
|View full text |Cite
|
Sign up to set email alerts
|

Early Discontinuation and Related Treatment Costs After Initiation of Basal Insulin in Type 2 Diabetes Patients

Abstract: Aims:The aim was to compare early discontinuation and related treatment costs in type 2 diabetes in primary care after initiation of insulin glargine or human basal insulin (NPH). Methods: Overall, 2765 glargine and 1554 NPH patients from 1072 general practices were analyzed (Disease Analyser). Early discontinuation was defined as switching to a different basal insulin or another insulin treatment regimen within 90 days after first basal insulin prescription (index date, ID). Treatment costs were assessed 365 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…This result was mainly driven by a significant increase in pharmacy costs in persistent versus nonpersistent patients (US$5,571 vs US$2,931; P <0.001) that was not offset by a reduction in medical costs (ambulatory and ER visits, inpatient, and other costs) (US$3,103 vs US$4,516; P =0.047) 20. Anderten et al found that, while the annual cost difference for DM-related prescriptions was lower in German patients with T2DM who persistently used insulin glargine compared with patients who switched insulin type, this failed to reach statistical significance 13. Similarly, total treatment costs (DM-related prescriptions and other medical services) were lower but not significantly different between persistent and nonpersistent insulin glargine patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was mainly driven by a significant increase in pharmacy costs in persistent versus nonpersistent patients (US$5,571 vs US$2,931; P <0.001) that was not offset by a reduction in medical costs (ambulatory and ER visits, inpatient, and other costs) (US$3,103 vs US$4,516; P =0.047) 20. Anderten et al found that, while the annual cost difference for DM-related prescriptions was lower in German patients with T2DM who persistently used insulin glargine compared with patients who switched insulin type, this failed to reach statistical significance 13. Similarly, total treatment costs (DM-related prescriptions and other medical services) were lower but not significantly different between persistent and nonpersistent insulin glargine patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacy/drug/medication costs were specifically reported as being included in the analyses of all studies, 13 reported including inpatient, hospitalization, and/or emergency room (ER) costs, and outpatient or ambulatory costs were reported in 10 studies. Some studies were, however, vague about what expenses were actually considered, instead just referring to “medical” or “total” costs in their methodologies 11,13–17. Only two studies considered the costs of nonadherence outside the health care system: patient co-payments were included in one study and out-of-pocket expenses were included in another 18,19.…”
Section: Resultsmentioning
confidence: 99%
“…Three focused on the period around insulin initiation. Costs for type 2 diabetes treatment in the year prior insulin initiation ranged between €757.00 and €843.07 and rose to €1277.85 up to €2204.41 after insulin initiation (48,52). Costs for the year around insulin initiation (6 months prior and 6 months after initiation) amount between €1828.43 and €1844.00, respectively (48,51).…”
Section: Diabetes Costs In Germanymentioning
confidence: 99%
“…Higher direct healthcare costs were reported for patients with longer disease duration (56). For France as well as for Germany, patients treated with insulin caused higher costs than patients treated without insulin (43,48,51,52,56,62,64).…”
Section: Cost Drivers In France and Germanymentioning
confidence: 99%
“…2). Eine Therapiekostenanalyse aus Deutschland ergab, dass der durchschnittliche Kostenunterschied zwischen diabetesbedingten Verschreibungen fĂĽr diejenigen, die weiterhin Glargin einnahmen, geringer war als fĂĽr diejenigen, die auf andere Behandlungsmethoden umstellten [64].…”
Section: Introductionunclassified